Stop and go traffic to tune T cell responses. - Dustin, M (2004)
Adaptive immune responses are initiated by interactions of T cells with antigen-presenting cells, but the basic nature of these interactions during an immune response in vivo has been a matter of speculation. While some in vitro systems provide evidence for stable interactions, referred to as immunological synapses, compelling evidence supports T cell activation through serial transient interactions. Deep tissue intravital and organ culture microscopy studies suggest that both modes of interaction are employed, but new issues have emerged. This review will discuss in vitro results that framed the hypotheses that are currently being tested in vivo. I present a model in which TCR stop signals compete with chemokine-mediated go signals to adjust the duration of immunological synapse formation and tune the immune response between tolerance and full activation.